RELATIONSHIP MARKETING, KUALITAS PELAYANAN, KEPUASAN DAN LOYALITAS PASIEN RUMAH SAKIT BALIMED DENPASAR - Ni Nyoman Mulyani (Jurnal Manajemen dan Bisnis, 2014)
The purpose of this study was to : 1 ) To determine and analyze the influence ofrelationship marketing on satisfaction Balimed Denpasar Hospital patients . 2 ) To identifyand analyze the influence of relationship marketing loyalty Balimed Denpasar Hospitalpatients . 3 ) To identify and analyze the impact of service quality on patient satisfactionBalimed Hospital Denpasar . 4 ) To identify and analyze the impact of service quality on loyaltyBalimed Denpasar Hospital patients . 5 ) To identify and analyze the effect of patientsatisfaction on loyalty pasein Balimed Hospital Denpasar .Respondents of this study were patients Balimed Denpasar Hospital totaling 210people . Collecting data in this study using a questionnaire containing 21 questions , eachquestion using 10 alternative answers . Analysis of the data used to answer research questionsand test hypotheses influence of relationship marketing , service quality , patient satisfactionand patient loyalty statistical methods used Structural Equation Modeling ( SEM ) with AMOSsoftware version 20The results showed that : 1) The better the relationship marketing , the higher levelof patient satisfaction verified . This means that the better the relationship marketing BalimedHospital Denpasar . 2) the better the higher the relationship marketing patient loyalty verified. 3 ) The better the quality of service , the higher level of patient satisfaction verified . 4 ) thebetter quality of service , the higher loyalty pasein is verified . 5 ) : the higher the level ofpatient satisfaction , the higher the patient's loyalty is tested.Keywords : relationship marketing , service quality , patient satisfaction and patient loyalty